Regulation of financial streams of technological modernization in the liberalization of the country's economy - A. O. Blinov; B. G. Khairov (Вестник СибАДИ, 2017)
The authors concluded that the impact of external economic factors on the Russian economy on a par with internal reinforces its uncertainty. In this study, the authors emphasize that exactly in Russia, the rapid processes of transformation of industrial policy determine the stability factors of achieving liberalization of the domestic economy. In this paper it is proposed to strengthen the socio-economic potential of the country due to the regulation of financial flows of technological modernization in the liberalized economy of the country.